Analisis Pengendalian Internal Account Payable di Sektor Perhotelan - Bunga Nada Aprilliandis; Dewi Khrisna Sawitri (OPTIMAL Jurnal Ekonomi dan Manajemen, 2026)
This study aims to analyze the effectiveness of internal control in the account payable (AP) process at Hotel XYZ Surabaya, a four-star hotel with a high volume of purchasing transactions. The research employs a descriptive qualitative method through interviews, observation of the “Tukar Tanda Terima” (TT) activity, and analysis of documents such as Purchase Orders (PO), Receiving Reports, and invoices. The analysis refers to the five COSO elements: control environment, risk assessment, control activities, information and communication, and monitoring. The findings indicate that the hotel has implemented segregation of duties, the three-way matching method, and multi-level authorization. However, several weaknesses remain, including delays in invoice submission, manual verification that is prone to errors, inefficient interdepartmental communication, and limited digital-based monitoring. This study recommends the adoption of an electronic approval system, enforcement of invoice deadlines, the use of a verification checklist during TT, and enhanced training and internal audits to strengthen the effectiveness of internal control in the account payable process.